Pelatihan Penulisan Jurnal Ilmiah Bagi Tenaga Pendidik (Guru SD) Di Kecamatan Siak Hulu Kabupaten Kampar - HADIYATI, HADIYATI; FATKHURAHMAN, FATKHURAHMAN (Komunitas Manajemen Kompetitif, 2017)
Abstract: Teachers as educators whose function is to provide knowledge to the learners. Teachers have a career ladder career path that is the basis for menggajian and also the provision of benefits in the form of functional allowance teacher certification. This certification requires teachers to be more professional in menrransfer knowledge in the classroom. Scientific journal is one of the tasks of teachers to rank IV A to IV b. This journal is a follow up of the results of a classroom action research that will be demolished to the level of local journals, journals of national and even international journals. But for teachers, rising to scientific journals alone be a good achievement. The problems faced by teachers in order to write an article that will be published to the scientific journal is the central issue. Teachers still do not have the knowledge and understanding in the realm of the task. The solution offered in this problem is the team will provide training in the form of writing articles that will be presented to a scientific journal. For the team, this time has had experience in managing several scientific journals, manuscripts from the collection process and until published manuscript. Training is given to teachers, teacher training is targeted to be able to write articles and can then be published to a scientific journal. This is very useful for teachers and is also useful for the team devotion in order to devote themselves to the public. Training is done in several stages, the first stage is the preparation phase, which prepares the trainee in this case is the cooperation partner. Then the second stage is the stage of provision of knowledge as an introduction and understanding of the administration in the form of examples and practices to the participants. Based on the results of community service performed may be explained the changes of knowledge, understanding and capabilities of participants in training there. Keywords: Scientific Journal Writing, Training For Labour Education (Teacher)